Effects of polyphenolic maqui (Aristotelia chilensis) extract on the inhibition of NLRP3 inflammasome and activation of mast cells in a mouse model of Crohn’s disease-like colitis - Ortiz-Cerda, Tamara; Argüelles-Arias, Federico; Macías-García, Laura; Vázquez-Román, Victoria; Tapia, Gladys; Xie, Kangzhe; García-García, María Desirée; Merinero, Manuel; García-Montes, Josefa-María; Alcudia, Ana; Witting, Paul K.; De-Miguel, Manuel (Frontiers in Immunology, 2024)
Introduction Crohn’s disease (CD) involves activation of mast cells (MC) and NF-кB in parallel with the PPAR-α/NLRP3 inflammasome/IL-1β pathway in the inflamed colon. Whether polyphenols from maqui (Aristotelia chilensis) represent a natural alternative treatment for CD is unclear. Therefore, we used an animal model of 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced CD-like colitis to investigate protective effects of maqui extract through monitoring NLRP3 inflammasome and MC activation in colon tissue. Methods Maqui extract was administered via orogastric route to mice after (post-Treatment group) or prior (pre-Treatment group) to TNBS-induction. Colon pathology was characterized by histoarchitectural imaging, disease activity index (DAI), and assessing NF-кB, p-NF-кB, PPAR-α/NLRP3 expression and IL-1β levels. Results Compared to mice treated with TNBS alone administration of anthocyanin-rich maqui extract improved the DAI, colon histoarchitecture and reduced both colon wet-weight and transmural inflammation. Induction with TNBS significantly increased colonic NLPR3 inflammasome activation, while co-treatment with maqui extract (either post- or pre-Treatment) significantly downregulated NLRP3, ASC and caspase-1 levels, which manifested as reduced colonic IL-1β levels. Supplemented maqui extract marginally diminished NF-кB activity in epithelial cells but reached statistical significance in immune cells (as judged by decreased NF-кB phosphorylation). PPAR-α signaling was largely unaffected by Maqui whereas MC infiltration into the colon mucosa and submucosa decreased and their level of degranulation was suppressed. Conclusion These outcomes show the post- and pre- Treatment effect of a polyphenolic extract rich in anthocyanins from maqui the acute phase of TNBS- induced CD-like colitis is linked to suppression of the NLRP3 inflammasome and reduced MC responses. These data indicate that maqui extract represents a potential nutraceutical for the treatment of inflammatory bowel disease (IBD).